2018
DOI: 10.3390/nu10020146
|View full text |Cite
|
Sign up to set email alerts
|

Bone Response to Dietary Co-Enrichment with Powdered Whole Grape and Probiotics

Abstract: Nutrition is a primary modifiable determinant of chronic noncommunicable disease, including osteoporosis. An etiology of osteoporosis is the stimulation of bone-resorbing osteoclasts by reactive oxygen species (ROS). Dietary polyphenols and probiotics demonstrate protective effects on bone that are associated with reduced ROS formation and suppressed osteoclast activity. This study tested the effect of dietary enrichment with powdered whole grape and probiotics (composed of equal parts Bifidobacterium bifidum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 106 publications
(153 reference statements)
1
16
0
Order By: Relevance
“…Target species of rats were Sprague-Dawley in 10 studies [ 32 41 ], C57BL/6J mice in 9 studies [ 42 50 ], Wistar rat in 5 studies [ 51 55 ], and BALB/c mice in 5 studies [ 56 59 ]. The other studies used senescence-accelerated mouse (SAMP) [ 60 , 61 ], virgin fisher rat [ 62 ], and ND4 Swiss Webster retired breeder mice [ 63 ]. Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Target species of rats were Sprague-Dawley in 10 studies [ 32 41 ], C57BL/6J mice in 9 studies [ 42 50 ], Wistar rat in 5 studies [ 51 55 ], and BALB/c mice in 5 studies [ 56 59 ]. The other studies used senescence-accelerated mouse (SAMP) [ 60 , 61 ], virgin fisher rat [ 62 ], and ND4 Swiss Webster retired breeder mice [ 63 ]. Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other studies used senescence-accelerated mouse (SAMP) [ 60 , 61 ], virgin fisher rat [ 62 ], and ND4 Swiss Webster retired breeder mice [ 63 ]. Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ]. In fourteen investigations, female rats had ovariectomy surgery that induced osteoporosis [ 36 , 37 , 39 , 40 , 42 , 44 , 47 , 51 , 56 , 57 , 59 , 62 , 66 ], and in two studies, diabetic rats were included [ 38 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is a major public health burden in our ageing population [6]. Bone undergoes turnover continuously, and the immune system is regulating this process since 1980 [7].…”
Section: Review Of Textmentioning
confidence: 99%
“…On the other hand, it is important to note that, in contrast with the reported benefits of probiotics on bone health, a recent study [6] showed that dietary enrichment with powdered whole grape and probiotics (composed of equal parts Bifidobacterium bifidum, B. breve, Lactobacillus casei, L. plantarum , and L. bulgaricus ) exerted either no effect on bone microarchitecture in a mouse model of age-related osteoporosis. However, this negative effect was attributed to possible differences in probiotic strains, the small sample size and the duration of the supplementation.…”
Section: Review Of Textmentioning
confidence: 99%
“…Polyphenols are a family of natural organic molecules, widely present in plant-derived foods. They are characterized, as the name indicates, by the presence of one or more phenolic groups, organized in more or less complex structures, generally of high molecular weight [7].…”
Section: Introductionmentioning
confidence: 99%